Women with perinatal suicidal ideation–A scoping review of the biopsychosocial risk factors to inform health service provision and research - Ann-Marie Bright; Owen Doody; Teresa Tuohy (PLoS ONE, 2022)
Objectives This review aims to map the existing evidence on perinatal suicidal ideation, identify biopsychosocial risk factors associated with suicidal ideation and make recommendations for service provision and future research. Methods Scoping review guided by Arskey’s and O’Malley’s (2005) framework. Five academic databases (PsycINFO, MEDLINE, CINAHL, ASSIA and Academic Search Complete) were searched from 1st January 2009 to 1st April 2022. Studies were screened by title, abstract and full text against inclusion and exclusion criteria. Primary qualitative, quantitative and mixed-methods studies, written in English pertaining to perinatal suicidal ideation were included. Forty-one studies met the eligibility criteria, data were extracted and narratively synthesised. Findings are reported in accordance with the PRISMA-SR extension. Key conclusions Findings were mapped onto the biopsychosocial framework and include sleep deprivation, maternal age, pregnancy complications, mood disorders, intimate partner violence, childhood maltreatment/abuse, low socioeconomic status, alcohol and tobacco misuse, miscarriage/perinatal loss, birth trauma and sleep deprivation. The findings demonstrate that the biopsychosocial risk factors for perinatal suicidal ideation are varied and complex. Implications for practice The minimisation of women’s experiences may lead to detrimental consequences and there is a need for increased knowledge of mental health problems by those working with women in the perinatal period to ensure safety planning conversations occur with every woman meeting ‘at risk’ criteria.